Secondary metabolites from the bark of Goniothalamus giganteus and their cytotoxic activities / Siti Nor Aisyah Abd Rahman - Siti Nor Aisyah , Abd Rahman (2024)
Styryl lactones, which are ubiquitous in the genus Goniothalamus, have emerged as promising anticancer agents due to their ability to induce apoptosis in the targeted cells. Therefore, this study aimed to rapidly identify styryl lactones from the bark of Malaysian plant, Goniothalamus giganteus, by combining traditional phytochemical methods with 13C-NMR-based dereplication analysis. From the 13C-NMR-based dereplication analysis of G. giganteus using the MixONat software, a total of nineteen compounds were identified, including sixteen styryl lactones; altholactone 2, goniobutenolide A 3, goniobutenolide B 4, 8-acetylgoniofufurone 5, goniofufurone 9, goniofupyrone 12, goniopypyrone 15, 8-epimer of goniobutenolide A 27, 3-acetyl-6,7-dihydroxy-6,7-dihydro-altholactone 68, 7-epi-goniobutenolide B 69, 3-acetyl-6,7-diacetoxy-6,7-dihydro-altholactone 71, dihydrogoniothalenol 74, digoniodiol 81, crassalactone D 83, 8-epi-9-deoxygoniopypyrone acetate 85, and (2R,3R,3aS,7R,7aS)-3-hydroxy-7-isopropoxy-2-phenyltetrahydro-2H-furo[3,2-b]pyran-5(6H)-one 86, two terpenes; stigmaterol 58 and poriferasterol 63, and one flavonoid; pinocembrin 59. Purification exercise led to the isolation of thirteen compounds including two new compounds; goniogigantone A 61 and goniogigantone B 62 (bis-styryllactone skeleton), together with eleven known compounds; altholactone 2, goniobutenolide A 3, 8-acetylgoniofufurone 5, 8-epi-goniofufurone 6, goniofufurone 9, goniopypyrone 15, 8-acetylgoniotriol 24, cardiobutanolide 26, stigmasterol 58, pinocembrin 59, and chrysin 60. Being the major compound in this species, altholactone 2 had showed the highest cytotoxic effect against both oral cancer cell lines, H103 and H400 with IC50 values of 5.81 μM and 5.08 μM, respectively.